Painless Anesthesia in Pediatric Dentistry: A Review - Sonali Bhuyan1 , Susant Mohanty2 , Sulagna Pradhan1 , Mrinali Shukla1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pain management is one of the most commonly faced problem for dentists while handling of pediatricpatients. A positive dental attitude can be instilled in a child if pain is handled properly. In recent times,various advancements and research have been made in the field of local anesthesia. These techniques alongwith the conventional ones can be utilized for better handling of pain and to get better apprehension frompatients. This review article is to discuss recent advancements in painless anesthetic techniques and toimprove the quality of treatment regarding pain in pediatric dentistry. As management of pain is of paramountimportance to instill a positive attitude about dentistry in children.